The Role of Islamic Religious Teachers in Shaping the Character of Morals in the Digital Era at Mts Aisyiyah North Sumatra - Mawar Dinur; Nurul Fadilla; Arlina, Arlina; Amelia Putri; Fadlan Fajri Harahap (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
This research explains several roles of teachers in forming akhlakul karimah character in the digital era at Mts Aisyiyah North Sumatra. The type of research used in this paper is descriptive qualitative. Then for data collection techniques using reading literature sources from books and from various journals related to the title of this discussion. This research aims to explore the role of teachers towards students in the digital era. In the digital era, teachers have a very important role in helping students develop good digital literacy skills. Teachers need to provide students with an understanding of wise use of technology, online privacy and digital security. The results of this research show that the role of Islamic teachers is in forming akhlakul karimah character by providing role models to their students, communicating and interacting with them both in class and outside of class. There are several strategies that can be pursued, namely: the current young generation needs to be introduced to a comprehensive understanding of the concept of morals, role models, preventing students from getting lost in pleasure and luxury, strengthening relationships between educators and students, building and controlling the student environment, finally forming morals using various methods that suit the students' conditions.